ChemInform Abstract: Prodigiosin Alkaloids: Recent Advancements in Total Synthesis and Their Biological Potential. Issue 16 (April 2015) - Nisha, Nisha; Kumar, Kewal; Kumar, Vipan
Abstract Review: [122 refs.